2022
DOI: 10.1111/jce.15669
|View full text |Cite
|
Sign up to set email alerts
|

The hemodynamic effect of simulated atrial fibrillation on left ventricular function

Abstract: Introduction Atrial fibrillation (AF) is the most common sustained arrhythmia in humans. The onset of the arrhythmia can significantly impair cardiac function. This hemodynamic deterioration has been explained by several mechanisms such as the loss of atrial contraction, shortening of ventricular filling, or heart rhythm irregularity. This study sought to evaluate the relative hemodynamic contribution of each of these components during in vivo simulated human AF. Methods Twelve patients undergoing catheter abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The irregular contractions during AF impair the atrium’s pumping function, leading to decreased blood flow speed and increased risk of blood stasis and thrombus formation in patients with NVAF 30 . Prior research has demonstrated a strong link between LAT/SEC and left atrial hemodynamic parameters 31 . Fang et al discovered that these parameters can help assess stroke risk in NVAF patients by indicating the association between thrombosis risk and blood flow status in the left atrium and left atrial appendage 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The irregular contractions during AF impair the atrium’s pumping function, leading to decreased blood flow speed and increased risk of blood stasis and thrombus formation in patients with NVAF 30 . Prior research has demonstrated a strong link between LAT/SEC and left atrial hemodynamic parameters 31 . Fang et al discovered that these parameters can help assess stroke risk in NVAF patients by indicating the association between thrombosis risk and blood flow status in the left atrium and left atrial appendage 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus new onset AF may be a marker of risk factors, which are known to affect EF recovery and increase heart failure risk. However direct hemodynamic effects of AF caused by the loss of atrial contraction, heart rate irregularity and increased heart rate may negatively influence EF recovery ( 40 ). Whether targeting patients with new onset AF can decrease mortality risk and improve EF after MI needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…AF is known to have a negative prognostic impact on CAD patients; 15 yet, it remains unclear if the 7 increased mortality is due to increased coronary ischemic events or from unfavorable hemodynamic effects, such as loss of atrial kick, high ventricular rate, and decreased cardiac output. 16 Several studies have attempted to understand the impact of both diseases. While previous studies have explored the associated poor outcomes, no study has directly examined the pattern of diagnostic workup, intervention, and cardiac outcomes in this sub-population.…”
Section: What Are the Clinical Implicationsmentioning
confidence: 99%
“…AF is known to have a negative prognostic impact on CAD patients; 15 yet, it remains unclear if the increased mortality is due to increased coronary ischemic events or from unfavorable hemodynamic effects, such as loss of atrial kick, high ventricular rate, and decreased cardiac output. 16…”
Section: Introductionmentioning
confidence: 99%